CP-029 Pim-check used by physicians to reduce drug related problems in internal medicine. (25th February 2017) - Blanc, AL; Guignard, B; Desnoyer, A; Grosgurin, O; Marti, C; Samer, C; Bonnabry, P
Abstract : Background: Drug related problems (DRPs) are important issues for inpatient safety and may contribute to adverse drug events and hospital costs. Potentially inappropriate medication (PIM), including over prescription (medication without a valid indication), under prescription (failure to prescribe a clinically indicated drug) and mis-prescription (unwanted drug interaction; incorrect prescribing) is a risk factor for DRPs. PIM-Check (www.pimcheck.org ), a prescription screening checklist, was recently developed to detect PIM in internal medicine patients. Purpose: This study aimed to determine if electronic application of PIM-Check, used by physicians, can decrease DRPs in internal medicine patients. Material and methods: This was an open label prospective study, conducted in two consecutive periods of 1 month, in patients admitted for ≥48 hours to seven internal medicine wards in a university hospital. In period 1, patients were treated with usual care (control group). In period 2, patients were treated with usual care preceded by a medication review performed by chief residents within 24 hours after admission using the PIM-Check electronic application (intervention group). At 48 hours, all medications, laboratory results, comorbidities and diagnoses were collected. DRPs were identified by a 'gold standard' group, composed of a clinical pharmacist, clinical pharmacologist and two internal medicine consultants, analysing all patient datasets (blinded to period group). Results: 297 patients were included: 188 in the control group and 109 in the intervention group. 909 DRPs (mean/patient ±SD: 3.1±2.2) were identified: 3.2±2.2 in the control group and 2.9±2.2 in the intervention group (p=0.21). Both groups were comparable (age, sex, number of drugs, comorbidities) and had similar mean DRPs/patient. The top 5 active compounds involved in DRPs were: esomeprazole, paracetamol, tobacco, aspirin and thiamine. In the intervention group, the mean number of statements suggested by PIM-Check was 13.9±7/patients. Among the 311 DRPs identified in this group, 33.4% were suggested by PIM-Check but no treatment modifications were performed by prescribers. Conclusion: PIM-Check allowed identification of one-third of DRPs. However, the number of DRPs did not decrease significantly in the intervention group. This lack of impact may be explained by the high number of statements displayed and the reluctance of hospital physicians to modify the treatment plan established by the general practitioner for chronic medical conditions, especially in the first 48 hours of hospitalisation. No conflict of interest